Monitoring Climate Finance and ODA - World Bank (Washington, DC, 2014)
The first major part of this paper focuses on tracking, monitoring, and reporting various types of flows, primarily from ODA (Official Development Assistance) and other public sources but also from private sources. It briefly reviews available information on various current and upcoming financial and investment flows to support climate action in developing countries as a first step in assessing the challenges associated with monitoring such flows. It considers both climate finance (the amount of additional resources required to catalyze the shift of a much larger volume of public and private development investments to climate friendlier options) and underlying finance (the almost 10 to 20 times larger amount of financial and investment flows in developing countries that must increasingly focus on climate action). The next part of the paper focuses on possible ways of tracking additionality in ODA flows, with the aim of stimulating a discussion within the World Bank Group (WBG) and its partners on this issue. It describes the various perceptions of different groups of countries as well as possible baselines, benchmarks, and tools for tracking progress. Increasingly reliable, comprehensive, and transparent reporting is needed to demonstrate that new climate finance instruments are not introduced at the expense of those targeting other objectives. The final section provides proposals for further action by industrial and developing countries, the U.N. system and multilateral development banks (MDBs).